SUV of (68Ga)DOTATOC-PET/CT predicts response probability of PRRT in neuroendocrine tumors - Kratochwil, Clemens; Stefanova, Melsa; Mavriopoulou, Eleni; Afshar-Oromieh, Ali; Mier, Walter; Haberkorn, Uwe; Giesel, Frederik L. (Molecular imaging & biology, 2015)
PurposeThe goal of our study was to quantify the expression of the somatostatin receptors (SSTR2) using the maximum standardized uptake value (SUVmax) of [68Ga]DOTA(0)-Phe(1)-Tyr(3)-octreotide (DOTATOC) positron emission tomography (PET)-computed tomography (CT) in liver metastases of patients with neuroendocrine tumors (NETs) prior to peptide receptor radiation therapy (PRRT) and compare the initial tumor uptake with the final treatment outcome.ProceduresSSTR2 expression of the 60 liver metastases in 30 NET patients was assessed at baseline and after PRRT by measuring SUVmax, tumor to spleen ratio (T/S ratio), and tumor to liver ratio (T/L ratio). Based on morphological changes and tumor size measured at baseline and follow-up contrast-enhanced CT (after three cycles of PRRT), lesions were divided into two groups by the following: (i) responding (n = 40) and (ii) non-responding (n = 20).ResultsStatistically significant differences were observed in the mean SUVmax for non-responding vs. responding lesions at baseline (18.00 ± 3.59 vs. 33.55 ± 4.62, p < 0.05) and for the mean T/S ratio (1.20 ± 0.37 vs. 1.90 ± 0.45, p < 0.05) and the mean T/L ratio (3.15 ± 0.53 vs. 4.97 ± 0.62, p < 0.05). Using the receiver operating characteristic curves, SUVmax was found a better metric than both T/L ratio and T/S ratio (area under the curve (AUC) of SUVmax 0.87; T/L ratio 0.78; T/S ratio 0.73) as a stratification criterion. Using a threshold value of >16.4 for SUVmax, the sensitivity and specificity in predicting responding lesions were 95 and 60 %, respectively.ConclusionWe propose a SUVmax cutoff of >16.4 from [68Ga]DOTATOC-PET-CT to select patients for PRRT. A T/L ratio >2.2 might present a scanner-independent criterion that enables the translation of our results to other institutions. However, the robustness of this arbitrary unit still needs to be evaluated with different PET scanners.